In vitro antioxidant and antityrosinase activities of Manilkara kauki - Srisupap Sirinada; Chaicharoenpong Chanya (Acta Pharmaceutica)
Manilkara kauki L. Dubard is a tropical plant in the genus Manilkara of family Sapotaceae. This study investigated the total phenolic and flavonoid contents, and antioxidant and antityrosinase activities in different parts of M. kauki (fruits, leaves, seeds, stem barks and woods) and in fractions of stem barks. The total phenolic and flavonoid contents of the methanol and aqueous crude extracts of different parts of M. kauki ranged from 10.87 to 176.56 mg GAE (gallic acid equivalents) per gram of crude extract and 14.33 to 821.67 mg QE (quercetin equivalents) per gram of crude extract, resp. Leaves and stem barks exhibited higher total phenolic and flavonoid contents and antioxidant and anti-tyrosinase activities than fruits, seeds and woods. Stem barks were sequentially extracted with n-hexane, ethyl acetate, methanol and water and then the fractionated extracts were subjected to antioxidant and antityrosinase activities testing. The ethyl acetate and methanol extracts of stem barks exhibited higher total phenolic and flavonoid contents and antioxidant and antityrosinase activities than the n-hexane and aqueous extracts. Moreover, ethyl acetate extract of M. kauki stem exhibited the highest antityrosinase activity. It may be a potential source of tyrosinase inhibitors for pharmaceutical and cosmetic applications.